تعليم مهارة القراءة في ضوء النظرية البنائية الاجتماعية لفيجوتسكي دراسة الحالةفي جامعة بالنجكارايا الإسلامية الحكومية - Aulia Mustika Ilmiani (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2017)
AbstrakOne of the lecturers in the Department of Arabic at IAIN Palangka Raya teaches the reading using newest way and innovation compared to the previous ones. The innovation contains a variety of learning materials, learning strategies and learning evaluation.From this phenomenon, the researcher concluded that in reading skill teaching as done by one of the lecturers at IAIN Palangka Raya, there are some indicators of learning that are based on Vigotsky